Linking 3D Soil Structure and Plant-Microbe-Soil Carbon Transfer in the Rhizosphere - Vidal, Alix; Hirte, Juliane; Bender, S. Franz; Mayer, Jochen; Gattinger, Andreas; Höschen, Carmen; Schädler, Sebastian; Iqbal, Toufiq M.; Mueller, Carsten W. (Frontiers in Environmental Science, 2018)
Plant roots are major transmitters of atmospheric carbon into soil. The rhizosphere, the soil volume around living roots influenced by root activities, represents hotspots for organic carbon (OC) inputs, microbial activity, and carbon turnover. Rhizosphere processes remain poorly understood and the observation of key mechanisms for carbon transfer and protection in intact rhizosphere microenvironments are challenging. We deciphered the fate of photosynthesis-derived OC in intact wheat rhizosphere, combining stable isotope labeling at field scale with high-resolution 3D-imaging. We used nano-scale secondary ion mass spectrometry and focus ion beam-scanning electron microscopy to generate insights into rhizosphere processes at nanometer scale. In immature wheat roots, the carbon circulated through the apoplastic pathway, via cell walls, from the stele to the cortex. The carbon was transferred to substantial microbial communuties, mainly represented by bacteria surrounding peripheral root cells. Iron oxides formed bridges between roots and bigger mineral particles, such as quartz, and surrounded bacteria in microaggregates close to the root surface. Some microaggregates were also intimately associated with the fungal hyphae surface. Based on these results, we propose a conceptual model depicting the fate of carbon at biogeochemical interfaces in the rhizosphere, at the forefront of growing roots. We observed complex interplays between vectors (roots, fungi, bacteria), transferring plant-derived OC into root-free soil and stabilizing agents (iron oxides, root and microorganism products), potentially protecting plant-derived OC within microaggregates in the rhizosphere.